Worry and associated cognitive features in Italian university students: Does gender make a difference?. (1st May 2018) - Bottesi, Gioia; Martignon, Anna; Cerea, Silvia; Ghisi, Marta
Abstract: Worry is frequently observed in undergraduates, especially in female students who usually show a lower adjustment to college life than male ones. The current study explored gender differences in worry and its associated cognitive features in a large sample of Italian university students and assessed whether different mechanisms may occur in the path from Intolerance of Uncertainty (IU) to worry according to gender. A sample made up of 243 male and 406 female undergraduates entered the study. Comparisons on measures assessing worry, IU, Positive Beliefs about Worry (PBW), Negative Problem Orientation (NPO), and Cognitive Avoidance (CA) were performed. Furthermore, two moderated mediation models (one for each sample) wherein IU was the independent variable, worry the dependent variable, PBW, NPO, and CA parallel mediators, were tested. Females showed higher levels of worry, NPO, and CA than males, but effects were small. Whilst PBW and NPO, but not CA, mediated the relationship between IU and worry in both samples, IU moderated the mediations only in females. Overall, results suggest the existence of a differential interplay between worry and associated cognitive features according to gender in Italian undergraduates. Highlights: Females usually show a lower adjustment to college life than males. Gender differences in the interplay between worry and cognitive features emerged. Intolerance of Uncertainty differently moderates the path to worry according to gender.